PEMANFAATAN BONGGOL PISANG BATU DAN KEPOK TERHADAP PERFORMANCE AYAM RAS PEDAGING - Aswandi (JURNAL TRITON, 2016)
Problems difficulties for livestock feed raw materials, one of the solutions look for alternative feed ingredients that have the potential quantitative and qualitative. The potential of the banana weevil is a high carbohydrate content and low crude fiber, thus can be used as an energy source feed material. The aim of research comparing the value of the benefit composition weevil feed containing flour banana plants Stone and Kepok with feed that does not contain flour banana weevil (commercial ), on broiler. The variables measured in this study are variable tackiness consisting of : 1 ) Feed consumption, 2 ) Added Weight Loss,3 ) Feed Conversion, 4 ) The weight of the carcass, while the economic variables consisted of : net gain. The research material implementation of data collection conducted maintenance of broiler for 30 ( thirty ) days, the study used 192 broiler chicks (DOC) of males and females Strain CP 707, at the end of the study a total of 32 chickens cuts , consisting of the respective chicken rations each treatment were taken at random, to determine the weight carcass, treatment P0 ( control) commercial ration, P2 ( 60 % Br I + 30 % flour banana weevil Stone and Kepok + 10 % Fish Meal ), P3 ( BR -I 70 % + 20 % flour banana weevil stone and Kepok + 10 % fish meal and P3 ( BR - I 80 % + 10 % flour banana weevil stone and Kepok + 10 % fish Meal ) . the design used was a completely randomized design ( CRD ) consisting of four treatments and four replications. Flour conclusion banana weevil Kepok stone and canbe used as a mixture of commercial ration ( BR - I) broiler until the level of 30 % . Body weight gain of broiler of each ration treatment P0 (control) P1, P2 and P3, respectively 58.75 g / head / day, 54.65 g / head / day, 51.95 g / head / day and 48.68 g / head / day. Use rations containing flour banana weevil Kepok and Stone by 30 % in the commercial feed mixes provide the most advantages.